Triple Button Line Implementation Through Corporate Social Responsibilty Program at PT. Semen Tonasa - Nur Sandi Marsuni; Darwis Said; Aini Indrijawati (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2022)
This study aims to explain and interpret the Corporate Social Responsibility practices of PT Semen Tonasa (Persero) Tbk which are implemented in the